ADAPTASI ORGANISASI TERHADAP PERKEMBANGAN ARSITEKTUR KOMPUTER MODERN - Andy Satria; Alya Prita Simbolon; Wita Kristika Purba (Asosiasi Dosen Muda Indonesia, 2023)
The rapid advancements in modern computer architecture pose significant challenges for organizations to remain relevant and efficient. This article explores the adaptation strategies implemented by organizations in response to the evolving landscape of contemporary computer architecture. The primary focus is on organizational efforts to align technological infrastructure, business processes, and organizational culture to support operational effectiveness. The discussion encompasses digital transformation, organizational cultural shifts, change management, cybersecurity, and the integration of new technologies as key elements in the adaptation strategy. By detailing the challenges and solutions applied, this research provides profound insights into how organizations can optimize their performance through intelligent adaptation to the developments in modern computer architecture. The findings of this study offer practical guidance for organizational leaders in designing successful adaptation strategies in this ever-changing era.